Spatial determinants of the mandibular curve of Spee in modern and archaic Homo. Issue 2 (27th June 2016) - Laird, Myra F.; Holton, Nathan E.; Scott, Jill E.; Franciscus, Robert G.; Marshall, Steven D.; Southard, Thomas E.
Abstract: Objectives: The curve of Spee (COS) is a mesio‐distally curved alignment of the canine through distal molar cusp tips in certain mammals including modern humans and some fossil hominins. In humans, the alignment varies from concave to flat, and previous studies have suggested that this difference reflects craniofacial morphology, including the degree of alveolar prognathism. However, the relationship between prognathism and concavity of the COS has not been tested in craniofacially variant populations. We tested the hypothesis that greater alveolar prognathism covaries with a flatter COS in African‐American and European‐American populations. We further examined this relationship in fossil Homo including Homo neanderthalensis and early anatomically modern Homo sapiens, which are expected to extend the amount of variation in the COS from the extant sample. Methods and Materials: These hypotheses were tested using three‐dimensional geometric morphometrics. Landmarks were recorded from the skulls of 166 African‐Americans, 123 European‐Americans, and 10 fossil hominin mandible casts. Landmarks were subjected to generalized Procrustes analysis, principal components analysis, and two‐block partial least squares analysis. Results: We documented covariation between the COS and alveolar prognathism such that relatively prognathic individuals have a flatter COS. Mandibular data from the fossil hominin taxa generally confirm and extend this correlation across a greater range of facial size and morphology in Homo . Discussion: Our results suggest that the magnitude of the COS is related to a suite of features associated with alveolar prognathism in modern humans and across anthropoids. We also discuss the implications for spatial interactions between the dental arches.